Estudio de factibilidad para la creación de una microempresa (leche, queso y yogurt) láctea en la provincia de Cotopaxi, cantón Pujilí, barrio Juan Salinas, en el periodo 2014-2015 - Chuquilla Toaquiza, Silvia Judith (2015)
This paper entitled "Feasibility study for the creation of a micro dairy company in the province of Cotopaxi, Pujilí, Juan Salinas neighborhood" arises to take advantage of the substantial amount of existing raw material in the sector. This research is the analysis of milk production at national, provincial and local levels, allowing know and identify areas with higher production capacity and culture of consumption of dairy products. Later market research is done to identify the tastes and preferences of consumers. Prior to the analysis of supply and demand is determined that there is an unmet demand in the market. Technical study, which will serve to establish the requirements, location and optimal plant size for the company was conducted. The financial study that the budget of costs and revenue was established.